Linking Authentic Leadership to Transactive Memory System, Team Innovativeness, and Selling Performance: A Multilevel Investigation - Asim Shahzad, Muhammad; Iqbal, Tahir; Imad Ud Din Akbar, Muhammad; Bakhsh, Khuda; Ahmad, Bilal (Frontiers in Psychology, 2022)
In today’s complex selling environment, it is challenging for sales leaders to enhance the effectiveness of their sales teams. The aim of this study is to observe the impact of authentic leadership on salespersons’ internal and external behaviors under B2B selling context [i.e., transactive memory system (TMS), innovative work behavior, and customer-directed OCB] and their consequences in team selling performance. Respondents of our survey included salespersons and managers working in the sales departments of pharmaceutical companies. By using structural equation modeling, the dyad responses from 348 matched salespeople–managers were analyzed. The findings disclose that authentic leadership behavior has a stronger relationship with the TMS, innovative work behavior, and customer-directed OCB. Our results also indicate that innovative work behavior and customer-directed OCB are potentially mediated between authentic leadership and team selling performance relationship. The theoretical implication of these results for managerial practice is also discussed.